Adventure/qualified tourism in the rehabilitation of juveniles - Wioletta Łubkowska; Małgorzata Paczyńska-Jędrycka (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2013)
The objective of this article was to show the educational values of adventure tourism in the process of rehabilitation of juveniles. Theoretical considerations concerning this topic give rise to the following conclusions: 1. Thanks to qualified tourism, young people shape their character and face weaknesses. It helps to change the behavior and create pro-social attitudes. 2. Qualified tourism teaches basic life skills. All of the above-mentioned points prove that part of correctional facilities activity should be based on qualified tourism.